2008
DOI: 10.1093/humrep/den113
|View full text |Cite
|
Sign up to set email alerts
|

Fas receptor is not present on ejaculated human sperm

Abstract: There is no detectable quantity of Fas on human ejaculated sperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
14
0
2
Order By: Relevance
“…Caspase-8 was activated to a certain level, most probably as a result of caspase ''cross talk'' (Grunewald et al, 2005c;Paasch et al, 2004b). These results were confirmed in a very recent study (Perticarari et al, 2008) suggesting that spermatozoal mitochondria are extremely susceptible to specific agonists of apoptosis. Betulinic acid molecules are currently being used experimentally in anticancer treatments, their side effects on the male reproductive system should be carefully considered.…”
Section: Triggers and Inhibitors Of Caspase Activation In Human Spermsupporting
confidence: 66%
See 1 more Smart Citation
“…Caspase-8 was activated to a certain level, most probably as a result of caspase ''cross talk'' (Grunewald et al, 2005c;Paasch et al, 2004b). These results were confirmed in a very recent study (Perticarari et al, 2008) suggesting that spermatozoal mitochondria are extremely susceptible to specific agonists of apoptosis. Betulinic acid molecules are currently being used experimentally in anticancer treatments, their side effects on the male reproductive system should be carefully considered.…”
Section: Triggers and Inhibitors Of Caspase Activation In Human Spermsupporting
confidence: 66%
“…While recent studies deny the presence of the Fas receptors on human sperm (Perticarari et al, 2008), earlier studies detected it on the surface of subsets of ejaculated spermatozoa using various techniques like western blotting and immuncytochemistry (Grunewald et al, 2001;Sakkas et al, 1999). However, their functional impact is unclear.…”
Section: Triggers and Inhibitors Of Caspase Activation In Human Spermmentioning
confidence: 99%
“…In the majority of the studies, Fas was not found on ejaculated sperm cells in normozoospermic men, [23][24][25] or if present, only in low percentages. 26 Some studies did not even observe Fas on spermatozoa from infertile men 23 or only at low percentages.…”
Section: Discussionmentioning
confidence: 93%
“…26 Some studies did not even observe Fas on spermatozoa from infertile men 23 or only at low percentages. 25 Studies have found Fas-positive sperm cells in infertile men, and reported inverse relationships between Fas and normal sperm cell morphology, concentration and motility. 14,24,26 These findings indicate that abortive apoptosis may have taken place.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors suggested that the Fas system is important in eliminating defective spermatozoa, but can show irregularities in sperm quality [27]. Also, Perticarari et al explained that the presence of Fas on ejaculated sperm is due to abortive apoptosis [60].…”
Section: Discussionmentioning
confidence: 99%